EVALUASI PROGRAM PRAKTIK PROFESI KEGURUAN TERPADU (PPKT) - AHMAD SOFYAN (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2012)
The objective of the research is to evaluate the implementation of the Integrated Teachers Profession Practice (PPKT) in the Faculty of Sciences and Teachers Training, State Islamic Univeristy (FITK UIN Jakarta). The research was conducted at the faculty and in several schools. The research was conducted from February to August in the academic year 2008/2009. The evaluation design used in this research was Discrepancy Evaluation Model (DEM) with a descriptive analysis. Source of data obtained from: 1) dean FITK, 2) the program manager, 3) supervisor, 4) principals and teachers tutors, 5) students because they can provide the required data in this study than is supported by the records / documents. Based on results above, it can be concluded that the conducting of PPKT program is ‘good enough’. Based on the conclusion, it can be addressed suggestion that PPKT program can be continued while paying more attention on several aspects of improvements.